AL-GHILAH'S POLICIES AND PRACTICES IN THE PERSPECTIVE OF ISLAMIC LAW - Julianti Julianti (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2020)
This research is motivated by the attention of the author who has studied a book of interpretation, namely the book "al-Qur'an and its Tafsir", compiled by the Ministry of Religion of the Republic of Indonesia. The issue of concern for breastfeeding mothers during pregnancy has an impact on the fate of the mother's life and her health because the burdens caused by pregnancy or childbirth can cause the mother to suffer, in addition to parents' fear of reproductive health as well as children's health and children's education due to economic factors that can bring kufr. Whereas in Islam, a family that plans to limit children to a certain number, for example only two in each family, is against Islamic law, natural law, and the wisdom of Allah creating humans in this world to reproduce and take advantage of this nature for human welfare. So that the focus of the study in this study leads to) BKKBN policies, al-ghilah practices in society as well as Islamic legal views about the NTB Provincial BKKBN policies regarding al-ghilah and its practices in society.